What Pediatric Dentists Need to Know about Coronavirus Disease (COVID-19) - Kanupriya Rathore (Shiraz University of Medical Sciences, 2020)
COVID-19, a viral disease fatal yet preventable is caused by a newly identified β-corona virus. The people most vulnerable to this infection are the ones with a prior history of diseases, low immunity, or either too old or too young (particularly children and infants). In the context of the virus's impact on the pediatric age groups, this article highlights some of the challenges and guidelines on managing it. Pediatric groups, like everyone else, are highly vulnerable to the infection by COVID-19. The lower number of pediatric patients involved at the beginning of a pandemic does not necessarily mean that children are less vulnerable to the infection. However, the good news is that the disease usually has a mild course and appropriate prevention and oral health management in children can help to keep it at bay. Adherence to simple compliance and safety protocols can go a long way. For instance, in the course of some of the procedures performed by a pediatric dentist, there may be a risk of aerosols being generated, which in turn can lead to cross-infection making the patient vulnerable to contracting COVID-19. In such a situation, parents are advised to take good home-based care and take telemedicine consultation immediately. This article lays a concrete emphasis on reviewing the limited published literature that is specific to the pediatric population regarding epidemiology, pathogenesis, diagnosis, and treatment modalities of COVID-19. It analyzes the potential risk from COVID-19 associated with pediatric dental treatment. In addition, it presents a series of considerations on potential oral prevention strategies on the management of urgent and non-urgent dental procedures in a context of disease transference control. This literature review also gives an insight for the private practitioner to have healthier management in the pediatric fraternity during this highly contagious COVID-19 pandemic.